In situ codoping of a CuO absorber layer with aluminum and titanium: the impact of codoping and interface engineering on the performance of a CuO-based heterojunction solar cell. (19th August 2016) - Masudy-Panah, Saeid; Radhakrishnan, K; Ru, Tan Hui; Yi, Ren; Wong, Ten It; Dalapati, Goutam Kumar
Abstract: Aluminum-doped cupric oxide (CuO:Al) was prepared via an out-diffusion process of Al from an Al-coated substrate into the deposited CuO thin film upon thermal treatment. The effect of the annealing temperature on the structural and optical properties of CuO:Al was investigated in detail. The influence of Al incorporation on the photovoltaic properties was then investigated by preparing a p-CuO:Al/n-Si heterojunction solar cell. A significant improvement in the performance of the solar cell was achieved by controlling the out-diffusion of Al. A novel in situ method to co-dope CuO with Al and titanium (Ti) has been proposed to demonstrate CuO-based solar cells with the front surface field (FSF) design. The FSF design was created by depositing a CuO:Al layer followed by a Ti-doped CuO (CuO:Ti) layer. This is the first successful experimental demonstration of the codoping of a CuO thin film and CuO thin film solar cells with the FSF design. The open circuit voltage ( V oc ), short circuit current density ( J sc ) and fill factor (FF) of the fabricated solar cells were significantly higher for the FSF device compared to devices without FSF. The FF of this device improved by 68% through the FSF design and a record efficiency ɳ of 2% was achieved. The improvement of the solar cell properties is mainly attributed to the reduction of surface recombination, which influences the charge carrier collection.